(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to know the reality of classroom leadership skills for teaching sports management in the Department of Physical Education and Sports Science from the point of view of third stage students. The fields of research consisted of third-year students in the Department of Physical Education and Sports Sciences / College of Basic Education. The research was applied for the period from 1/2/2022 - 24/4/2022. In the classrooms of the Department of Physical Education and Sports Sciences / College of Basic Education/ Al-Mustansiriyah. The most prominent conclusions were that sports administration professors possess different leadership skills in the field of teaching and correct leadership within the classroom. And My teacher of sports management has an effective leadership personality in the classroom. Sports administration professors have the ability to properly and deliberately plan the lesson in advance. The most prominent recommendations are to encourage participation with Iraqi and local universities in order to exchange experiences with them in order to renew and increase acquaintance between them. The faculty members must be properly included in the leadership preparation courses in order to properly enhance their leadership ability in the classroom. And assessing the leadership skills of faculty members in colleges and departments of physical education and sports sciences from the students’ point of view